Time-resolved volatile profiles and molecular-species lipid remodeling during lipase treatment of anhydrous milk fat - Anqi Chen; Qingyun Xu; Jiaming Li; Yanxi Chen; Qiance Shen; Guocheng Du; Jianghua Li; Jian Chen (Food Research International, 2026)

Potential of individual-scale phenological measurements for improving wood productivity and maintaining genetic diversity in forest management - Haruka Sano; Tai-Shen Chen; Jiaming Yan; Naoko Miura; Minoru Inamori; Wei Guo; Sachiko Isobe; Kazutaka Kusunoki; Hiroyoshi Iwata (Forest Ecology and Management, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Generalized traverse task scheduling based on THRO algorithm for AUV with energy-constrained - Qixin Sha; Rui Nian; Jiaming Zhang; Xiaoting Xu; Yue Shen; Bo He (Ocean Engineering, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Evaluation of Groundwater Origin, Quality, and Potential Health Risks in the Ordos Coal Mine Base, Northwest China: Insights from Geochemical and Isotopic Approaches - Jiaming Zhou; Keyi Zhang; Tenglin Deng; Zilong Liao; Bing Xu; Fei Gao; Quandong Lian; Jianghong Yan; Shen Qu (Mine Water and the Environment, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Targeting Strategies of Stem Cell-Derived Extracellular Vesicles in the Treatment of Cardiovascular Diseases - Jiaming Fan; Liyun Yao; Jiayi Yao; Shumin Jiang; Lianbo Shao; Yunfang Mo; Ziying Yang; Zhenya Shen (Stem Cell Reviews and Reports, 2026)

Spatiotemporal changes in global cropland fire activity from 2003 to 2020 - Jiaming Wang; Xiaoting Zhong; Jie Zhao; Xiaofan Shen; Mengyu Wang; Junhao He; Xiaohan Meng; Qiuling Chen; Xinrui Lu; Liang Wang; Chao Yue (Global and Planetary Change, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Hydrophilic and lipophilic diblock polymer-based co-delivery nanoplatform for impossible mission: Resistance management toward insecticides via Nrf2-sMaf pathway - Jiajia Zhao; Zeng Wang; Jiaming Yin; Ying Wei; Mingshan Li; Jialin Gou; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Insight shift from laboratory to industrialization for tail gas-based ethanol production - Jiaming Gu; Danfeng Wang; Qun Shen; Li Shang; Guofei Shen; Nannan Sun; Shuhuan Tong; Wei Chao; Yangyang Guo; Wei Wei (Chemical Engineering Journal, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Task-Sequencing Optimization Using DSSA Algorithm for AUV with Limited Endurance - Qixin Sha; Jiaming Zhang; Yue Shen; Bo He (Journal of Marine Science and Engineering, 2025)
Efficiency is very important for robots when executing multiple tasks, especially for autonomous underwater vehicles (AUVs) with limited endurance. In order to improve efficiency, task-sequencing optimization, which focuses on achieving the optimal execution order of multiple tasks, is one effective way. In this paper, the classic lawnmower traverse task is taken as an example for optimization, and discrete salp swarm algorithm (DSSA), which combines salp swarm algorithm (SSA) and genetic algorithm (GA), is selected and applied to optimize task sequencing for one AUV. In the optimization process, there are two key problems that need to be solved. One is how to encode the individual chromosome and the other is how to perform genetic operations on chromosomes of different lengths. For the former problem, a two-layer encoding method is proposed to generate individuals in the population, in which identity number and entry point of different areas are encoded, respectively. For the latter problem, mutation and crossover operators are modified and extended to deal with individuals of variable length due to the limited endurance of AUVs. Simulation results show that the sequencing optimization can be achieved after finite iteration. Through comprehensive comparison, DSSA is finally implemented and verified in a physical AUV.

Enhancing cancer-killing activity of PMN transfusion therapy via apoptotic modulation function of selenium nanoparticles - Chenyu Lin; Jing Wang; Yuqian Zhu; Dachuan Zhang; Xixi Huang; Jiaming Wang; Jianlin Ren; Ming Hou; Mufan Wu; Bing Shen; Bingdi Chen (Chemical Engineering Journal, 2025)

Phytoextraction of Soil Cadmium by Vetiveria zizanioides Dead Shoots - Wenwen Li; Ning Liu; Xiaoling Tan; Ruoyao Shen; Jiaming Yu; Jie Li; Khateeb Hussain; Shiyong Yang (Bulletin of Environmental Contamination and Toxicology, 2025)

Genome-wide identification of the SmPHR gene family in Salvia miltiorrhiza and SmPHR7-mediated response to phosphate starvation in Arabidopsis thaliana - Xinxin Wang; Renjun Qu; Shiwei Wang; Jiaming Peng; Juan Guo; Guanghong Cui; Tong Chen; Meilan Chen; Ye Shen (Plant Cell Reports, 2025)

Preparation of a smart nano-herbicide MP@HLDP with strong permeability performance improves herbicidal activity while reducing the adverse impacts - Xile Deng; Zeng Wang; Jiaming Yin; Zhichao Dong; Jie Shen; Shuo Yan; Lianyang Bai (Chemical Engineering Journal, 2025)

Fish Community Diversity and Spatiotemporal Dynamics in the Downstream of the Fujiang River Based on Environmental DNA - Jiaming Zhang; Yifang Chen; Xinxin Zhou; Jiaxin Huang; Xiaohan Dong; Shuli Zhu; Yanjun Shen (Fishes, 2025)
Hydrological changes caused by dam construction are among the primary drivers of global freshwater biodiversity decline. To assess the current status of fish community diversity and examine the impacts of cascade hydropower development on fish diversity, this study employed environmental DNA (eDNA) technology from 2023 to 2024 to conduct seasonal surveys at 18 sampling sites across six river segments separated by five dams in the downstream section of the Fujiang River. The study aimed to uncover the temporal and spatial dynamics of fish diversity and community structure, as well as to analyze the influence of environmental factors on these patterns. The results identified 84 fish species spanning 60 genera, 19 families, and 7 orders, including 2 nationally protected species, 11 endemic species of the upper Yangtze River, and 13 alien species. The cascade dams were found to have significantly reduced fish diversity compared to historical records, with a marked decline in native species and a rise in alien species, contributing to the miniaturization and homogenization of fish communities. Environmental factor analysis revealed that chemical oxygen demand (COD), dissolved oxygen (DO), total dissolved solids (TDS), electrical conductivity (EC), and reservoir formation time were significant drivers of fish community structure and diversity. This study provides essential baseline data on fish diversity under the influence of cascade hydropower development in the Fujiang River. It also offers valuable insights into the current status of fish resources and supports efforts in fish conservation and aquatic ecosystem management in the region.

Mapping QTLs for stigma exsertion-related traits in two sets of CSSL populations of Oryza sativa cultivars using RSTEP-LRT method - Chunyu Jing; Mei Hai; Jiaming Shen; Xinru Li; Mengyuan Zhang; Changmin Hu; Qing Xu; Jianhua Jiang; Xiaojing Dang (Euphytica, 2025)

Insights into the effects of environmental factors on phytoplankton and microzooplankton at a basin scale: diversity, assembly mechanisms, and co-occurrence networks - Yanjun Shen; Xinxin Zhou; Jiaming Zhang; Qinghua Li; Yufeng Zhang; Qing Zuo (Frontiers in Marine Science, 2024)
Mastering the characteristics of planktonic microbial communities under the influence of basin-scale environmental factors can provide scientific basis to develop more targeted protection and restoration measures. Here, an environmental DNA metabarcoding technology was applied to investigate the phytoplankton and microzooplankton simultaneously along the whole basin of Jialing River, one of the most important rivers in Southwest China with large scale altitude gradient and water temperature discrepancy. Along the river-way from upper to lower reach, an upward trend in richness of both phytoplankton and microzooplankton was observed with significant positive and negative correlations to water temperature and altitude (Spearman correlation, p < 0.05), respectively. Significant variations in their compositions along the river were also uncovered with Chrysophyta and Foraminifera was potential keystones recognized by the co-occurrence network analysis. Additionally, exponential distance-decay of similarities were detected for both phytoplankton and microzooplankton, which were stronger for phytoplankton. Based on the results of variation partitioning analysis and null model, variations in phytoplankton communities were more governed by environmental selection than those in microzooplankton. Furthermore, the co-occurrence network showed a declining trend in the complexity and stability from the upper to lower reaches. These findings could serve to establish a basis for the investigation of phytoplankton and microzooplankton communities in rivers with multiple artificial modifications.

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Environmental DNA (eDNA) reveals the effects of cascade dam development on the distribution patterns of aquatic biodiversity in mountain rivers - Yanjun Shen; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Ruli Cheng (Frontiers in Marine Science, 2024)
The rich and special biodiversity in mountain rivers is experiencing a continuous decline due to the influence of climate change and anthropogenic factors. To explore the alterations in the distribution of aquatic biodiversity in mountain rivers in the context of cascade dam development, the environmental DNA (eDNA) metabarcoding technique was used to examine the aquatic biodiversity of the Wujiang River, a representative mountain river with an 11-stage cascade dam. In this study, a comprehensive analysis of aquatic organisms in the Wujiang River mainstem was conducted, and 17 phyla and 38 classes were detected in the 36 water samples. The most abundant group is the benthic organisms, and the least abundant group is the amphibians. The results of the diversity analysis showed a clear longitudinal distribution pattern of aquatic organisms along the altitudinal gradient, with higher richness of aquatic organism communities the further to the lower reaches. Meanwhile, RDA analysis revealed that altitude, dissolved oxygen, reservoir length, and reservoir construction time were the key environmental factors influencing the distribution of aquatic organisms in the Wujiang River mainstem. The findings of this research also showed the applicability of the eDNA method in detecting aquatic biodiversity.

Quasi-homogeneous photoelectrochemical organic transformations for tunable products and 100% conversion ratio - Cheng Lin; Yuan Lu; Jiaming Miao; Zhongyuan Ma; Youngmoon Choi; Yan Yang; Chaoran Dong; Jinyou Shen; Jong Hyeok Park; Kan Zhang (Science Bulletin, 2024)

Numerical research on the influence of ocean conditions on the transient response of passive decay heat removal system of the floating Fluoride-Salt-Cooled High-Temperature Reactors - Limin Liu; Ziyin Liu; Jiaming Zhang; Cong Shen; Maolong Liu; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2024)

Preparation of salicylic acid nano-protectant with dual synergistic mechanism: High direct fungicidal activity and plant defence toward cotton Verticillium wilt - Jiaming Yin; Jiajia Zhao; Zeng Wang; Fan Xue; Qi Wang; Huiming Guo; Hongmei Cheng; Jie Li; Jie Shen; Meizhen Yin; Xiaofeng Su; Shuo Yan (Chemical Engineering Journal, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Development of CaCl2·6H2O-mannitol/SiO2 shape-stabilized composite phase change material for the radiant cooling panel system - Jiaming Zhang; Haiwen Li; Yanliang Du; Tao Xu; Ting Zou; Shen Wei; Dongqiao Zhang (Energy and Buildings, 2024)

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Carbon emissions and low-carbon development in Olefin industry - Qun Shen; Jiaming Gu; Li Shang; Shuang Liu; Xuehang Song; Weisheng Yu; Yongping Liu; Nannan Sun; Wei Wei (Environmental Research, 2024)

An experimental study of mitigating coastal dune erosion by using bio-carbonization of reactive magnesia cement - Jiaming Zhang; Yuhao Li; Yi Luo; Yanjun Li; Qinggang Yang; Zijian Shen (Marine Georesources & Geotechnology, 2024)

Non-uniform milling caused by preferential orientation of rice grains in friction rice mills - Jiaming Fei; Wenyu Feng; Shaohang Shen; Yanlong Han; Anqi Li; Xianzhi Hao; Fuguo Jia; Ze Sun; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2023)

Numerical investigation of flow similarity of rice grains in friction rice mill and establishment of scale-up rule - Anqi Li; Fuguo Jia; Jiaming Fei; Yanlong Han; Peiyu Chen; Wenyu Feng; Xianzhi Hao; Shaohang Shen; Hao Li (Computers and Electronics in Agriculture, 2023)

Study on dynamic response mechanism of rice grains in friction rice mill and scale-up approach of parameter based on discrete element method - Anqi Li; Fuguo Jia; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Xianzhi Hao; Jiaming Fei; Shaohang Shen; Wenyu Feng (Innovative Food Science & Emerging Technologies, 2023)

Magnetic nanometer combined with microwave: Novel rapid thawing promotes phenolics release in frozen-storage lychee - Canhua Xu; Jiaming Lu; Qingzhu Zeng; Junjia Zhang; Lihong Dong; Fei Huang; Yingbin Shen; Dongxiao Su (Food Chemistry, 2023)

The mechanism of bran layer removal in friction rice mills - Jiaming Fei; Wenyu Feng; Fuguo Jia; Yanlong Han; Peiyu Chen; Anqi Li; Yinglong Wang; Jincheng Zhang; Shaohang Shen; Xianzhi Hao (Biosystems Engineering, 2023)

In-depth understanding of catalytic and adsorbing effects in polysulfides conversion and rationally designing coaxial nanofibers for Li-S batteries - Jiaming Tian; Zihan Shen; Huiting Cheng; Xin Jin; Zhonghua Li; Yang Wen; Junfeng Hui; Shaohua Guo; Huigang Zhang; Qingshan Zhu (Chemical Engineering Journal, 2023)

Improving the detection accuracy of the nitrogen content of fresh tea leaves by combining FT-NIR with moisture removal method - Jiaming Guo; Han Huang; Xiaolong He; Jinwei Cai; Zhixiong Zeng; Chengying Ma; Enli Lü; Qunyu Shen; Yanhua Liu (Food Chemistry, 2023)

Breakage mechanism of brown rice grain during rubber roll hulling - Peiyu Chen; Fuguo Jia; Jincheng Zhang; Yanlong Han; Anqi Li; Yinglong Wang; Jiaming Fei; Shaohang Shen; Wenyu Feng; Xianzhi Hao (Biosystems Engineering, 2023)

Excess pore water pressure and seepage in slopes induced by breaking internal solitary waves - Zhuangcai Tian; Lei Jia; Jiaming Xiang; Guotao Yuan; Kun Yang; Jun Wei; Mingwei Zhang; Honglei Shen; Jianhua Yue (Ocean Engineering, 2023)

Numerical simulation approach for predicting rice milling performance under different convex rib helix angle based on discrete element method - Anqi Li; Fuguo Jia; Shaohang Shen; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Wenyu Feng; Jiaming Fei; Xianzhi Hao (Innovative Food Science & Emerging Technologies, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

HIV Tat Protein Induces Myocardial Fibrosis Through TGF-β1-CTGF Signaling Cascade: A Potential Mechanism of HIV Infection-Related Cardiac Manifestations - Yannan Jiang; Lu Chai; Hongguang Wang; Xiuyun Shen; Moyondafoluwa Blessing Fasae; Jinfeng Jiao; Yahan Yu; Jiaming Ju; Bing Liu; Yunlong Bai (Cardiovascular Toxicology, 2021)

Study of mosaicism of Pyropia yezoensis - Yuan He; Wei Zhou; Jiaming Li; Songdong Shen (Marine Biology Research, 2019)